PEMIDANAAN TERHADAP PIHAK YANG MENGABAIKAN PUTUSAN PENGADILAN AGAMA - Febriani, Lidya (UIN Fatmawati Sukarno Bengkulu, 2017)
The purpose of this research is to know the way of punishment against those who ignore the judgment of the religious court. This research uses the approach method used in legal research namely the normative juridical, that is a problem approach by examining and reviewing a legislation that is applicable and competent to is used as a basis for problem solving, so the steps in this study use juridical logic. In this study the authors collected data by in-depth interview method to 3 (three) judges of Bengkulu Religious Court. While the method of data analysis using the framework of inductive thinking is the way of thinking by taking conclusions from the data that is special. The result of this research is that the punishment against those who ignore the decision of the Religious Court, namely: the first, through civil law that the plaintiff can file the execution of the decision of the Religious Court to the defendant. Consequently, if the execution can be exercised, the right of the defendant will be forced to be handed over to the plaintiff with the value of the decision. While the second way is by the act of punishment where the plaintiff can file a criminal complaint criminal article embezzlement. This can be done when the defendant neglects to implement the breakup as set forth in Article 372 of the Criminal Code.